PELATIHAN PENELITIAN ETNOMATEMATIKA UNTUK GURU DAN PENELITI PEMULA - Hakim, Arif Rahman; M. Tohimin Apriyanto; Muhamad Farhan; Napis, Napis; Rahmatulloh, Rahmatulloh (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
Learning process standards for mathematics subjects including media selection, method selection, compiling learning modules, adjusting the context of the content of mathematics subject matter into student activities, and so on become the core of the problem in terms of process quality. These problems became the focus of the Community Service (PkM) team to offer solutions to Tashfiyah Tutoring to conduct training, guidance, and mentoring on the theory and practice of ethnomathematics research. This ethnomathematics research training activity for teachers and novice researchers was carried out at the Tashfiyah Tutoring Hall which is located at Jl. Swadaya II No.59, RT.1 / RW.5, Tj. Bar, Jagakarsa Sub-district, South Jakarta City, Special Capital Region of Jakarta 12530, Indonesia, attended by 15 participants. The series of activities in this training are: (1) Preparation stage; (2) Exposure stage regarding activity description; (3) Material delivery stage regarding ethnomathematics research; and (4) Discussion stage. The ethnomathematics research training for teachers and novice researchers that has been carried out is very useful for all participants, so as to increase the competence of the participants in terms of conducting ethnomathematics research and have a positive impact on all participants in activities that specifically understand ethnomathematics research.